Pengaruh Zakat, Pembiayaan Syariah, Sukuk, Terhadap Kemiskinan Dengan Pertumbuhan Ekonomi Nasional Sebagai Variabel Moderasi Di Indonesia - Zahrina Ghaisany Pulungan; Hendra Harmain; Laylan Syafina (CV. ITTC INDONESIA, 2023)
The aim of this research is to find out whether zakat has an effect on poverty in Indonesia. To find out whether sharia financing has an effect on poverty in Indonesia. To find out whether sukuk have an effect on poverty in Indonesia. To find out whether zakat, sharia financing and sukuk simultaneously influence national economic growth in Indonesia. To find out whether poverty is able to moderate the influence of zakat, sharia financing and sukuk on national economic growth in Indonesia. This research uses a quantitative approach with time series data carried out on several official websites. For data collection on the Zakat variable, data is accessed from https://baznas.go.id, while for sharia financing data it is accessed from https: https://ojk.go. id, then for education, APBN and Poverty accessed via https://bps.go.id, from 2015-2022. The data analysis techniques used are multiple regression and MRA (Moderated Regression Analysis). The results of this research are that the zakat variable influences poverty in Indonesia. Sharia financing variables influence poverty in Indonesia. The sukuk variable influences national economic growth in Indonesia. The variables zakat, sharia financing and sukuk simultaneously influence poverty in Indonesia. National economic growth is able to moderate the influence of zakat, sharia financing and sukuk on poverty in Indonesia.